2014
DOI: 10.1017/jns.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in food and nutrient intakes among young children and their mothers in rural Burkina Faso

Abstract: It is important to understand and account for seasonal variation in food and nutrient intakes when planning interventions to combat micronutrient deficiencies in resource-poor settings. The objective of the present study was to quantify food and nutrient intakes and assess the adequacy of micronutrient intakes among young children and their mothers during the lean and post-harvest (PH) seasons in rural Burkina Faso. We quantified food intakes by 24-h recall in a representative sample of 480 children aged 36–59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 19 publications
5
92
2
5
Order By: Relevance
“…Although our study did not investigate at individual level the direction of changes in intakes, we assume that, because on overall there was a decrease in the quality of the diet of the children from plenty season to lean season, this dietary change was rather a decrease. Other similar recent studies (Arsenault et al, ; M'Kaibi et al, ) and a recent meta‐analysis (Stelmach‐Mardas et al, ) have constantly reported increase in intakes from lean to plenty seasons. It is on this basis that we conclude that increasing nutritional knowledge would lead to relatively better and stable nutrient intakes and nutritional outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…Although our study did not investigate at individual level the direction of changes in intakes, we assume that, because on overall there was a decrease in the quality of the diet of the children from plenty season to lean season, this dietary change was rather a decrease. Other similar recent studies (Arsenault et al, ; M'Kaibi et al, ) and a recent meta‐analysis (Stelmach‐Mardas et al, ) have constantly reported increase in intakes from lean to plenty seasons. It is on this basis that we conclude that increasing nutritional knowledge would lead to relatively better and stable nutrient intakes and nutritional outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…The median probability of adequate folate intake was zero for women in both the lean and post-harvest seasons, and for children during the lean season, but the median probability of adequate folate intake rose to 0.98 in children in the post-harvest season (Arsenault et al, 2014). Folate intake in men and women in Ireland was assessed through a food frequency questionnaire and showed that 40% of the Irish population is below the recommended dietary allowance for folate (Harrington et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…To our knowledge, no global data are available on the prevalence of folate deficiency worldwide, although the deficiency has been detected in countries as different as Burkina Faso, Guatemala, Iran, Ireland, Thailand and United States (Arsenault et al, 2014;Assantachai and Lekhakula, 2007;Brunst et al, 2014;Harrington et al, 2008;Rosenthal et al, 2015;Sedehi, 2013 …”
Section: -1-folate Requirementsmentioning
confidence: 99%
“…To address this issue, some researchers reported the distribution of HHMs beforehand by field enumerators, and asked the participants to serve individual portions [40, 41]. However, Kigutha [42] hypothesized that this might affect eating habits of the subjects, and therefore introduce biases in individual intake estimation.…”
Section: Discussionmentioning
confidence: 99%